2003
DOI: 10.1152/ajprenal.00212.2002
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization of Western diet inhibits bone resorption independently of K intake and reduces cortisol secretion in humans

Abstract: A Western-type diet is associated with osteoporosis and calcium nephrolithiasis. On the basis of observations that calcium retention and inhibition of bone resorption result from alkali administration, it is assumed that the acid load inherent in this diet is responsible for increased bone resorption and calcium loss from bone. However, it is not known whether the dietary acid load acts directly or indirectly (i.e., via endocrine changes) on bone metabolism. It is also unclear whether alkali administration aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
139
1
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(149 citation statements)
references
References 51 publications
2
139
1
7
Order By: Relevance
“…Bicarbonate supplementation has been shown to increase insulin sensitivity among patients with kidney disease. 26 Further, Maurer and colleagues 6 showed that alkali supplementation decreased both serum cortisol levels and urinary cortisol excretion in a controlled metabolic study involving 9 people over 7 days. However, in a secondary analysis of a trial assessing bone outcomes in 153 people without diabetes aged 50 years and older who were administered alkali supplementation over 3 months, those who received bicarbonate supplementation did not have any change in fasting glucose, serum insulin level or insulin resistance as measured by the homeostasis model assessment for insulin resistance (HOMA-IR), nor was there any change in serum cortisol levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bicarbonate supplementation has been shown to increase insulin sensitivity among patients with kidney disease. 26 Further, Maurer and colleagues 6 showed that alkali supplementation decreased both serum cortisol levels and urinary cortisol excretion in a controlled metabolic study involving 9 people over 7 days. However, in a secondary analysis of a trial assessing bone outcomes in 153 people without diabetes aged 50 years and older who were administered alkali supplementation over 3 months, those who received bicarbonate supplementation did not have any change in fasting glucose, serum insulin level or insulin resistance as measured by the homeostasis model assessment for insulin resistance (HOMA-IR), nor was there any change in serum cortisol levels.…”
Section: Discussionmentioning
confidence: 99%
“…Diet exposures and physical activity were calculated as updated cumulative average levels as of the baseline (1990) questionnaire. We also summarized intake of cereal fibre and trans fats, glycemic load and the ratio of polyunsaturated to saturated fats (with each component categorized in quintiles and scored 1-5, where 5 was assigned to the healthiest intake) in a diabetes diet score (ranging from [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], with a high diet score associated with a reduced risk of type 2 diabetes mellitus in the Nurses' Health Study. 16 The reproducibility and validity of the food-frequency questionnaires have been described.…”
Section: Assessment Of Covariatesmentioning
confidence: 99%
“…In the studies in which the calciuric effects of metabolic acidosis were reduced with alkali treatment, urine pH increased to the 6.5 to 7 range, but plasma pH and bicarbonate values did not change (80,81,83,85). However, as shown in the two patients with the milk alkali syndrome presented in this review, urine pH values were higher than in the aforementioned studies, as were serum bicarbonate and arterial pH values.…”
Section: Kidneymentioning
confidence: 49%
“…Some studies of alkali treatment also have shown that the decrease in urine calcium excretion occurs independent of calcium regulatory hormones such as PTH and calcitriol. Whereas supplemental alkali treatment did not change plasma pH or bicarbonate levels, urine pH did increase from the 5.5 to 6 range to the 6.5 to 7.0 range (80,81,83,85). Therefore, the enhanced calcium reabsorption could be, at least in part, from an increase in luminal pH in the distal tubule.…”
Section: Kidneymentioning
confidence: 87%
“…Corresponding NaHCO 3 reductions also occur after dietary acid loading, i.e., through increases in potential renal acid loads (PRAL), biochemically measurable as renal NAE increases. The consequences of either form of low grade metabolic acidosis are increases in glucocorticoids, i.e., cortisol levels, as have been reported for high salt intake [10][11][12] and observed for dietary (orally) acidification in adults [13] as well as in children of our DONALD study [manuscript in preparation]. These glucocorticoid elevations are only of moderate magnitude, however in the long-term, if habitually high PRAL diets or high NaCl amounts are ingested-or even both are combined-an accordingly raised cortisol activity will not be without consequences.…”
mentioning
confidence: 68%